The Weight of Our Words: Language and Teacher Agency from the Perspective of Gee’s ‘Cultural Models’ - Ngee Derk, Tiong (The English Teacher, 2021)
In this article, I suggest that one way to enhance teacher agency is to practise greater linguistic awareness in our professional conversations. Based on a conceptual framework utilising the idea of ‘cultural models’ (everyday theories expressed in language) I analyse primary data of Malaysian English-language teachers’ meetings to show two ways in which they have an impact on practice and agency. Based on the evidence, I claim that cultural models [1] function as problem-framing devices and [2] can support transformations in practice. The data in this paper comes from audio- visual recordings of teacher meetings, generated as part of a larger study on teacher collaborative discourse in professional learning communities (PLC), with English-language teachers at Malaysian national secondary schools. Based on these findings, I argue that teacher agency— defined as the capacity to make a difference in the context of teachers’ work—is partly a function of how teachers speak about the relevant domains of their practice, be they students, subject or pedagogy. This offers practitioners who wish to be more agentic in their practice some relevant points for reflection.
Keywords: teacher agency, cultural models, social linguistics, professional learning communities, Malaysia